If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + -1x = -6(2x + 7) Reorder the terms: -9 + -1x = -6(7 + 2x) -9 + -1x = (7 * -6 + 2x * -6) -9 + -1x = (-42 + -12x) Solving -9 + -1x = -42 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. -9 + -1x + 12x = -42 + -12x + 12x Combine like terms: -1x + 12x = 11x -9 + 11x = -42 + -12x + 12x Combine like terms: -12x + 12x = 0 -9 + 11x = -42 + 0 -9 + 11x = -42 Add '9' to each side of the equation. -9 + 9 + 11x = -42 + 9 Combine like terms: -9 + 9 = 0 0 + 11x = -42 + 9 11x = -42 + 9 Combine like terms: -42 + 9 = -33 11x = -33 Divide each side by '11'. x = -3 Simplifying x = -3
| -5x+4x+20-10x= | | -11=7y+8(y+8) | | -22+6r=-8r-6(1-r) | | 2a+a=-21 | | (750-x)-600-y=3x-y | | 120.08=2808.97(r) | | (2y-80)=(y+9) | | 7(d-3)+6= | | (8x+12)=(10x-24) | | 3x-4+4x+8+x=180 | | (x+30)=(2x) | | 7x-4x+x-4+3x= | | 6.5x-5+x-1.2= | | 4b-6-9b-8= | | 682/d=21 | | (3x-15)=(2x+25) | | -5=5x+5y | | 50(t)=-16t^2+50o | | 50(t)=-16t^2+ho | | h(t)=-16t^2+ho | | 2(-8)-21(-8)-7= | | 25-15(-8)= | | 45=9/2h | | 25-15(8)= | | 45=1/2h(9) | | 2(8)-21(8)-7= | | ×=2/3 | | 9/7(M-19) | | -2x+3=5x-2 | | 7x^9/8-35=0 | | -7(3)+13= | | 2178=p(1+.03*7) |